ФОРМУВАННЯ СОЦІАЛЬНОЇ АКТИВНОСТІ ЯК ПРОВІДНА СКЛАДОВА СУЧАСНОЇ ПЕДАГОГІКИ (Педагогіка вищої та середньої школи, 2006)
In the article the problem of scientific approach is examined to organisation to the process of education of social activity of young people. On the basis analysis of researches in area of philosophy, sociology, psychophisiologe, history,. pedagogics the complex model of social activity is offered as factor of trunsinon of society on the new level of development.